2019
DOI: 10.1016/j.immuni.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Cell Survival and Cytokine Release after Inflammasome Activation Is Regulated by the Toll-IL-1R Protein SARM

Abstract: Assembly of inflammasomes after infection or injury leads to the release of interleukin-1b (IL-1b) and to pyroptosis. After inflammasome activation, cells either pyroptose or enter a hyperactivated state defined by IL-1b secretion without cell death, but what controls these different outcomes is unknown. Here, we show that removal of the Toll-IL-1R protein SARM from macrophages uncouples inflammasome-dependent cytokine release and pyroptosis, whereby cells displayed increased IL-1b production but reduced pyrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
128
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(130 citation statements)
references
References 51 publications
2
128
0
Order By: Relevance
“…Sterile α and HEAT Armadillo motif-containing protein (SARM) is a Toll-IL-1R domain-containing protein involved in cell death and innate immune responses. 53 SARM is required for the optimal induction of pyroptosis upon stimulation with nigericin, a classical NLRP3 activator. The precise mechanisms by which SARM enhances pyroptosis currently remain unclear; however, upon stimulation with nigericin, SARM clusters on mitochondria and mediates mitochondrial depolarization.…”
Section: Regulation Of Pyroptosismentioning
confidence: 99%
See 2 more Smart Citations
“…Sterile α and HEAT Armadillo motif-containing protein (SARM) is a Toll-IL-1R domain-containing protein involved in cell death and innate immune responses. 53 SARM is required for the optimal induction of pyroptosis upon stimulation with nigericin, a classical NLRP3 activator. The precise mechanisms by which SARM enhances pyroptosis currently remain unclear; however, upon stimulation with nigericin, SARM clusters on mitochondria and mediates mitochondrial depolarization.…”
Section: Regulation Of Pyroptosismentioning
confidence: 99%
“…54 SARM clustering and mitochondrial depolarization were not induced by a stimulation with peptidoglycan. 53 Therefore, it currently remains unclear whether SARM clustering and mitochondrial depolarization contribute to pyroptosis, and the mechanisms by which SARM is activated upon inflammasome formation need to be elucidated.…”
Section: Regulation Of Pyroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Labzin et al () found that NLRP3‐dependent lL‐1β secretion occurs in the absence of significant pyroptosis. This uncoupling of IL‐1β secretion and cell death is increasingly reported in the literature (Carty et al , ). How pyroptosis is limited in human macrophages is an intriguing conundrum, as it would be expected that active caspase‐1 will cleave both gasdermin‐D and pro‐IL‐1β.…”
Section: Trim21 Triggers Nlrp3 Activation In Response To Adenovirus Imentioning
confidence: 64%
“…is increasingly reported in the literature (Carty et al, 2019). How pyroptosis is limited in human macrophages is an intriguing conundrum, as it would be expected that active caspase-1 will cleave both gasdermin-D and pro-IL-1b.…”
mentioning
confidence: 99%